The Effect of Work Environment, OHS, and Job Satisfaction on Employee Performance: A Case Study of Private Defense Company in Indonesia - Jodia Ridha Arrozak; Agus Achmad Suhendra; Ilma Mufidah (International Journal of Innovation in Enterprise System, 2021)
Intense competition in Indonesia forces private companies in the defense industry to be morecompetitive. PT. Z is one of the largest private defense products and equipment manufacturer inIndonesia. To retain competitiveness, PT. Z must provide defense products and equipment with thebest quality and deliver it on-time. The quality and on-time delivery of products and equipmentfulfillment rely on the performance of employee at PT. Z. Over the last few years, employeeperformance at PT. Z constantly decreased. The decrease of employee performance can be causedby several factors including work environment, occupational health and safety, and job satisfaction.This research will examine the effect of work environment (WE), occupational health and safety(OHS) and job satisfaction (JS) on employee performance (EP). The analysis was carried out usingthe PLS-SEM with 120 samples taken from production and engineering division at PT. Z. The resultshows that there are positive and significant effect of WE on EP, WE on JS, OHS on JS, and JS onEP. JS also mediates the effect of OHS on EP. On the other hand, OHS does not have a direct effecton EP and JS cannot mediate the effect of WE on EP.